Titanium Defect Structure Change after Gas-Phase Hydrogenation at Different Temperatures and Cooling Rates; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Mikhaylov (Mikhailov) A. A. Andrey Anatolievich; Laptev R. S. Roman Sergeevich; Kudiyarov V. N. Victor Nikolaevich; Volokitina T. L. Tatiana Leonidovna (2016, 2016)
Title screen